Survival of Lactobacillus casei strain Shirota in the intestines of healthy Chinese adults. (May 2015) - Wang, Ran; Chen, Shanbin; Jin, Junhua; Ren, Fazheng; Li, Yang; Qiao, Zhenxing; Wang, Yue; Zhao, Liang
ABSTRACT Lactobacillus casei strain Shirota (LcS) is a widely used probiotic strain with health benefits. In this study, the survival of LcS in the intestines of healthy Chinese adults was assessed and the effects of LcS on stool consistency, stool SCFAs and intestinal microbiota evaluated. Subjects consumed 100 mL per day of a probiotic beverage containing 1.0 × 108 CFU/mL of LcS for 14 days. LcS were enumerated using a culture method and the colony identity confirmed by ELISA. Fourteen days after ingestion, the amount of LcS recovered from fecal samples was between 6.86 ± 0.80 and 7.17 ± 0.57 Log10 CFU/g of feces (mean ± SD). The intestinal microbiotas were analyzed by denaturing gradient gel electrophoresis. Principal component analysis showed that consuming LcS significantly changed fecal microbiota profiles. According to redundancy analysis, the amounts of 25 bacterial strains were significantly correlated with LcS intake (P < 0.05), 11 of them positively and fourteen negatively. Concentrations of acetic acid and propionic acid in feces were significantly lower during the ingestion period than during the baseline period (P < 0.05). These results confirm that LcS can survive passage through the gastrointestinal tract of Chinese people; however, they were found to have little ability to persist once their consumption had ceased. Furthermore, consumption of probiotic beverages containing LcS can modulate the composition of the intestinal microbiota on a long‐term basis, resulting in decreased concentrations of SCFAs in the gut.